Frequency and clinical impact of CDKN2A/ARF/CDKN2B gene deletions as assessed by in-depth genetic analyses in adult T cell acute lymphoblastic leukemia - E. Genescà; A. Lazarenkov; M. Morgades; G. Berbis; N. Ruíz-Xivillé; P. Gómez-Marzo; J. Ribera; J. Juncà; A. González-Pérez; S. Mercadal; R. Guardia; M. T. Artola; et al. (Journal of Hematology & Oncology, 2018)
Abstract Recurrent deletions of the CDKN2A/ARF/CDKN2B genes encoded at chromosome 9p21 have been described in both pediatric and adult acute lymphoblastic leukemia (ALL), but their prognostic value remains controversial, with limited data on adult T-ALL. Here, we investigated the presence of homozygous and heterozygous deletions of the CDKN2A/ARF and CDKN2B genes in 64 adult T-ALL patients enrolled in two consecutive trials from the Spanish PETHEMA group. Alterations in CDKN2A/ARF/CDKN2B were detected in 35/64 patients (55%). Most of them consisted of 9p21 losses involving homozygous deletions of the CDKNA/ARF gene (26/64), as confirmed by single nucleotide polymorphism (SNP) arrays and interphase fluorescence in situ hybridization (iFISH). Deletions involving the CDKN2A/ARF/CDKN2B locus correlated with a higher frequency of cortical T cell phenotype and a better clearance of minimal residual disease (MRD) after induction therapy. Moreover, the combination of an altered copy-number-value (CNV) involving the CDKN2A/ARF/CDKN2B gene locus and undetectable MRD (≤ 0.01%) values allowed the identification of a subset of T-ALL with better overall survival in the absence of hematopoietic stem cell transplantation.